(untitled) (Majalah Kedokteran Bandung, 2015)
Penanganan penyakit infeksi diperlukan suatu imunostimulator. Propolis adalah campuran resin yang dikumpulkan lebah dari tumbuh-tumbuhan, digunakan sebagai material isolasi sarang lebah, merupakan bahan yang berpotensi sebagai imunostimulator. Penelitian dilakukan di Laboratorium Penelitian dan Pengujian Terpadu Universitas Gadjah Mada, pada Januari–Maret 2013. Penelitian ini bertujuan menganalisis peningkatan aktivitas dan kapasitas fagositosis kultur makrofag yang diberi ekstrak etanol propolis terhadap Enteropathogenic Escherichia coli (EPEC). Desain penelitian eskperimen. Ke dalam kultur makrofag yang diperoleh dari tiga orang subjek, masing-masing diberi ekstrak etanol propolis 6,25, 12,5, 25, 50, dan 100 µg/mL serta kontrol tanpa ekstrak etanol propolis. Inkubasi dilakukan satu hari. Kultur diinfeksikan EPEC selama 30 menit, diwarnai dengan Giemsa dan diamati dengan mikroskop. Persentase aktivitas fagositosis diperoleh dengan menghitung jumlah makrofag yang aktif dalam 100 makrofag. Nilai kapasitas fagositosis diperoleh dengan menghitung jumlah bakteri yang difagosit oleh 50 makrofag. Uji analysis of variance (ANOVA) menunjukkan perbedaan signifikan aktivitas maupun kapasitas fagositosis kultur makrofag yang diberi ekstrak etanol propolis dibanding dengan kontrol (p=0,000). Uji Tukey HSD pada aktivitas fagositosis menunjukkan hasil signifikan antara kontrol dan konsentrasi 6,25 µg/mL (p=0,008), sedangkan pada kapasitas fagositosis terlihat antara kontrol dan konsentrasi 12,5 µg/mL (p=0,001). Simpulan, ekstrak etanol propolis meningkatkan aktivitas dan kapasitas fagositosis kultur makrofag terhadap EPEC dengan konsentrasi minimum 12,5 µg/mL. [MKB. 2015;47(2):102–8] Kata kunci: Aktivitas fagositosis, Enteropathogenic Escherichia coli (EPEC), kapasitas fagositosis, makrofag, propolis. The Effect of Ethanolic Extract Propolis on Phagocytosis Activity and Capacity Macrophages Culture which Infected by Enteropathogenic Escherichia coli (EPEC) Abstract The use of immunostimulant for treatment infectious diseases is needed. Propolis is mixture of resin collected from plants by bees, used as an insulating material in beehives, which has potential as immunostimulant. The research was performed at Laboratory of research and integrated testing Gadjah Mada University in Januaryâˆ’March 2013. This experimental research is amied to analyze the increase of phagocytosis activity and capacity on macrophages culture which added by propolis ethanolic extract againts Enteropathogenic Escherichia coli (EPEC). The design research is experimental. Macrophage culture obtained from three subjects, individually culture supplemented with the propolis ethanolic extract 6.25, 12.5, 25, 50, and 100 µg/mL as well as control without the addition of propolis ethanolic extract. The cultures were incubated for one day. Macrophage cultures infected by EPEC for 30 minutes, stained by Giemsa and observed by microscope. Percentage of phagocytosis activity is determined by the number of active macrophages per 100 macrophages. Phagocytosis capacity value determined by counting the number of bacteria that phagocytized by 50 macrophages. Analysis of variance (ANOVA) showed significantly different phagocytosis activity and capacity between macrophage cultures that added by propolis ethanolic extract and control (p=0.000). Tukey HSD analysis showed significantly different phagocytosis activity between control and subject with concentration 6.25 µg/mL (p=0.008) whereas on phagocytosis capacity appears between control and subject with concentration 12,5 µg/mL (p=0.001). In conclusion, propolis ethanolic extract is able to increase the phagocytosis activity and capacity of macrophages againts EPEC with minimum concentration 12.5µg/mL. [MKB. 2015;47(2):102–8] Key words: Enteropathogenic Escherichia coli (EPEC), macrophage, phagocytosis activity, phagocytosiscapacity, propolis DOI: 10.15395/mkb.v47n2.460